Psychological Condition of Nurses in the Aftermath of COVID-19 - Indonesian Nurses’ Perspective - Rokhman, Abdul; Hidayati, Nur; Ubudiyah, Masunatul (Babali Nursing Research, 2024)
Background: COVID-19 is a global pandemic that strikes various groups, including nurses. Nurses are the health workers who are most exposed to COVID-19. Besides causing physical symptoms, COVID-19 also brings psychological symptoms, which need to be studied more deeply. The purpose of this study was to investigate post-covid psychological impact on nurses from the perspective of Indonesian nurses. Methods: This study was conducted using a descriptive approach on 187 nurses working in health services in Lamongan Regency who were exposed to COVID-19 and selected by purposive sampling. Psychological conditions studied included depression, which was measured by the Patient Health Questionnaire-9 (PHQ-9); anxiety, measured by general anxiety disorder-7 (GAD-7); and insomnia, measured by the Sleep Condition Indicator (SCI). The data was collected from June to July 2022 using a Google form and analyzed descriptively.Results: The results showed that 55.1% of nurses were female, 87.7% were aged 22-45 years, 73.8% worked in hospitals, 87.2% worked in health services for more than 20 years, 81.8% smoked, and 18.2% were hospitalized when exposed to COVID-19. The results showed that 31.6% of nurses experienced mild to severe anxiety, 32.1% experienced mild to severe depression, and 9.1% experienced insomnia.Conclusion: Psychological symptoms experienced by nurses after being exposed to COVID-19 included anxiety, depression, and insomnia. Psychosocial stress factors and or pathophysiology of viral infections may trigger psychological disorders. Future researchers are recommended to examine further the factors contributing to psychological disorders in nurses and how long nurses experience post-covid psychological disorders.